2018
DOI: 10.1128/aem.02222-17
|View full text |Cite
|
Sign up to set email alerts
|

Methanogens Are Major Contributors to Nitrogen Fixation in Soils of the Florida Everglades

Abstract: The objective of this study was to investigate the interaction of the nitrogen (N) cycle with methane production in the Florida Everglades, a large freshwater wetland. This study provides an initial analysis of the distribution and expression of N-cycling genes in Water Conservation Area 2A (WCA-2A), a section of the marsh that underwent phosphorus (P) loading for many years due to runoff from upstream agricultural activities. The elevated P resulted in increased primary productivity and an N limitation in P-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 71 publications
2
37
0
Order By: Relevance
“…Although methanotrophs comprised less than 0.1% of the 16S rRNA, this alone does not exclude them from being a major contributor to N 2 fixation. Recently Bae et al ( 2018 ) showed that archaea constituting only 0.27% of the microbial community could account for 44% of the N fixed in an Florida peat system. In addition, N 2 fixation rates may differ over seasons (Lett and Michelsen 2014 ) and thus the microbial guilds actively performing N 2 fixation may vary with season.…”
Section: Discussionmentioning
confidence: 99%
“…Although methanotrophs comprised less than 0.1% of the 16S rRNA, this alone does not exclude them from being a major contributor to N 2 fixation. Recently Bae et al ( 2018 ) showed that archaea constituting only 0.27% of the microbial community could account for 44% of the N fixed in an Florida peat system. In addition, N 2 fixation rates may differ over seasons (Lett and Michelsen 2014 ) and thus the microbial guilds actively performing N 2 fixation may vary with season.…”
Section: Discussionmentioning
confidence: 99%
“…Increased sulfate reduction in response to saltwater intrusion is a common phenomenon [97] and may help to explain the high potential for nitrogen fixation observed in saltpan sediments, as nitrogen fixation can be coupled to sulfate reduction [98][99][100]. Some Euryarchaeota are also able to fix nitrogen and are beginning to be recognized for their contribution to organic nitrogen supply in soils [101]. These unexpected differences in potential energy and nutrient flows between saltpans and brackish and fresh marsh underscore the inferential nature of the current methods and imply that further functional as well as taxonomic investigation of saltpan sediments are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A melt curve analysis was conducted by increasing the temperature from 60 to 95°C by 0.5°C increments to verify the nonspecific amplification. The calculation of archaeal and bacterial amoA genes in the samples was based on a standard curve generated using standard plasmid DNA, which was made by cloning the target gene fragment as described by Bae, Morrison, Chanton, and Ogram (). The R 2 of qPCR standard curves was ≥.99, and the efficiency ( E ) was 84%–98% for AOA and 83%–90% for AOB, as calculated from the slope of the standard curve using the formula E = 10 (−1/slope) − 1.…”
Section: Methodsmentioning
confidence: 99%